Comprehensive metabolomic characterization of defense reprogramming in Castanea mollissima under Oligonychus ununguis feeding stress - Xinfang Zhang; Shuhang Zhang; Ying Li; Yan Guo; Jinyu Liu; Jiayi Liu; Liying Fan; Guangpeng Wang (PLoS ONE, 2026)
Piercing-sucking arthropods such as the chestnut red mite (CRM) Oligonychus ununguis impair leaf tissues by extracting nutrients from mesophyll cells, thereby lowering the photosynthetic capacity and nut yield in Chinese chestnut ( Castanea mollissima Bl.). Despite its economic significance, the metabolic mechanisms underlying chestnut responses to mite infestation remain poorly understood. Comparative leaf metabolomic analyses were conducted on four cultivars exhibiting different resistance levels to elucidate these mechanisms. The leaf chlorosis index was used to assess resistance, and three pairwise comparison groups were established accordingly. Secondary metabolomic profiling demonstrated that resistant varieties exhibited more pronounced metabolic reprogramming following infestation than susceptible cultivars. Among the secondary metabolites detected, flavonoids and phenolic acids were predominant. The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis identified numerous differentially accumulated metabolites (DAMs) associated with flavonoid, flavonol, and phenylpropanoid biosynthesis pathways. Remarkably, 27 phenylpropanoids and flavonoids were significantly accumulated in resistant cultivars but were largely undetected or showed no substantial variation in vulnerable cultivars. These findings indicate that specific phenylpropanoids and flavonoids, along with their corresponding biosynthetic networks, are integral to the resistance of the species against infestation by chestnut red mites. This study provides a metabolic foundation for breeding mite-resistant chestnut varieties.